Computer Simulation Studies in Condensed-Matter Physics XVIII Proceedings of the Eighteenth Workshop, Athens, GA, USA, March 7-11, 2005 - Landau, David P.; Lewis, Steven P.; Schüttler, Heinz-Bernd.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
This volume represents a "status report" emanating from presentations made during the 18th Annual Workshop on Computer Simulations Studies in Condensed Matter Physics at the Center for Simulational Physics at the University of Georgia in March 2005. It provides a broad overview of the most recent advances in the field, spanning the range from statistical physics to soft condensed matter and biological systems. Results on nanostructures and materials are included as are several descriptions of advances in quantum simulations and quantum computing as well as.methodological advances.
Computer Simulation Studies in Condensed Matter Physics: An Introduction -- Computer Simulation Studies in Condensed Matter Physics: An Introduction -- Quantum Simulations and Quantum Computing Nanostructures -- Quantum Monte Carlo Simulations of the Impurity-Induced Phase Transitions in Low-Dimensional Magnets -- Quantum World-line Monte Carlo Method with Non-binary Loops and Its Application -- Event-by-Event Simulation of Quantum Phenomena -- Deterministic Event-based Simulation of Universal Quantum Computation -- Materials and Nanostructures -- Unstable Crack Motion is Predictable -- First Principles Theory of Nano-Materials, Spintronic Materials, and Nano-Spintronic Materials -- Advances in Monte Carlo Simulations of Nanostructured Materials -- Molecular Dynamics Study of Atomic Displacements and X-Ray Diffuse Scattering -- Phase Transition and Other Topics in Statistical Mechanics -- A Note on Stable States of Dipolar Systems at Low Temperatures -- Low-Temperature Phase Boundary of Dilute Lattice Spin Glasses -- Simulation Study of Gas-Liquid Interface -- Dynamic Scaling of a Cluster Growth Process far from Equilibrium -- Analysis of the Blume-Capel Model with the Wang-Landau Algorithm -- Aging at Criticality in Models with Absorbing States -- Size Dispersity Effects on the Two-Dimensional Melting -- Methods -- Asynchronously Parallelised Percolation on Distributed Machines -- Applications of AViz in Undergraduate Education -- Synchronous Sublattice Algorithm for Parallel Kinetic Monte Carlo Simulations -- Performance and Improvements of Flat-histogram Monte Carlo Simulations -- Biological and Soft Condensed Matter -- Monte Carlo Study of the Isotropic-Nematic Interface in Suspensions of Spherocylinders -- Langevin Dynamics Study of Polymer Translocation through a Nanopore -- Invasive Allele Spread under Preemptive Competition.
Keywords: Condensed matter; Computer simulation; Logic design; Mathematical physics; Condensed Matter Physics; Simulation and Modeling; Logic Design; Theoretical, Mathematical and Computational Physics